Analisis Gerakan Forehand Pada Tenis Meja Di Klub PTM Elektra Kab Demak - Dyah Ismi Mukaromah; Husnul Hadi; Muh. Isna Nurdin (YLPK Mahardhika, 2020)
The background is because the athlete only uses a forehand to defend, whereas a forehand is good for attacking. The formulation of the problem, how to analyze the biomechanics of forehand motion in table tennis and how good hand movements, body position and leg position using forehand movements, whether the 9 angles of the movement affect the entry or absence of the ball. The aim of this research is to know how the biomechanical analysis of forehand motion in table tennis and to find out how good hand movement, body position and leg position using the forehand movement of the 9 angles affect the entry or absence of the ball. Based on processing using statistics, there is a significant difference in comparisons when the ball position hits the bet; 1) wrist position 167.875o-223.8o; 2) bending of the right elbow 82,9o-92,1o; 3) bending of the left elbow 86.24o-95.82o; 4) opening of the upper arm of the right hand 71.06o-78.95o; 5) opening of the upper arm of the left hand 45.45o-50.5o; 6) leaning body 145.54o-161.71o; 7) right leg bending 152.6o-169.5o; 9) distance of both feet 44.05o-48.94o. Keywords: Forehand, Table Tennis. ABSTRAK Latar belakang karena atlet hanya menggunakan pukulan forehand untuk bertahan, padahal pukulan forehand bagus untuk menyerang. Rumusan masalah, bagaimana analisis biomekanika gerakan forehand pada cabang olahraga tenis meja dan bagaimana gerakan tangan, posisi badan dan posisi kaki yang baik dengan menggunakan gerakan forehand apakah dari 9 sudut gerakan tersebut mempengaruhi masuk atau tidaknya bola. Tujuan penelitin ingin mengetahui bagaimana analisis biomekanika gerakan forehand pada cabang olahraga tenis meja dan untuk mengetahui bagaimana gerakan tangan, posisi badan dan posisi kaki yang baik dengan menggunakan gerakan forehand apakah dari 9 sudut gerakan tersebut mempengaruhi masuk atau tidaknya bola.Berdasarkan pengolahan dengan menggunakan statistik, terdapat perbedaan perbandingan yang signifikan saat posisi bola mengenai bet; 1) posisi pergelangan tangan 167,875o-223,8o; 2) tekukan siku kanan 82,9o-92,1o; 3) tekukan siku kiri 86.24o-95.82o ; 4) bukaan lengan atas tangan kanan 71,06o-78,95o ; 5) bukaan lengan atas tangan kiri 45,45o-50,5o; 6) kecondongan badan 145,54o-161,71o; 7) tekukan kaki kanan 152,6o-169,5o ; 9) jarak kedua kaki 44,05o-48,94o. Kata kunci: Forehand, Tenis Meja.